Transformation Design : Perspectives on a New Design Attitude - Jonas, Wolfgang; von Anshelm, Kristof; Zerwas, Sarah (Board of International Research in Design, 2015)
Transformation design is looking for new ways to change our behavior and society through new forms of innovation, and it has already leaded to a fruitful discourse. The book attempts to form an initial position in terms of this ambitious and ethical design perspective. It also seeks to inspire the international debate to push for a project of responsible design.